Resource-efficient photonic networks for next-generation AI computing - Ilker Oguz; Mustafa Yildirim; Jih-Liang Hsieh; Niyazi Ulas Dinc; Christophe Moser; Demetri Psaltis (Light: Science & Applications)
Abstract Current trends in artificial intelligence toward larger models demand a rethinking of both hardware and algorithms. Photonics-based systems offer high-speed, energy-efficient computing units, provided algorithms are designed to exploit photonics’ unique strengths. The recent implementation of cellular automata in photonics demonstrates how a few local interactions can achieve high throughput and precision.